Evolusi Pendidikan Kewarganegaraan: dari Pendekatan Berbasis Pengetahuan ke Perspektif yang Lebih Luas - Denda Ginanjar; Muhammad Firman; Isep Sunandi; Wandra Wardiansha Purnama; Nadila Maharani (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
This research aims to explore the evolution of civic education from a traditional knowledge-based approach towards a broader and more comprehensive perspective. The method used is a literature review by analyzing various sources, including scholarly journals, books, and official documents. The research findings indicate that civic education has undergone significant transformation in recent decades. The traditional approach focused on rote memorization has been replaced by a more holistic perspective emphasizing the development of critical thinking skills, civic participation, and social responsibility. This research contributes new insights by identifying the factors driving the evolution of civic education, as well as its implications for educational practice. In conclusion, civic education today must adapt to the changing times and prepare the younger generation to be active, critical, and responsible citizens.